The association between polymorphisms in RLIP76 and drug response in epilepsy. (December 2007) - Leschziner, Guy D; Jorgensen, Andrea L; Andrew, Toby; Williamson, Paula R; Marson, Anthony G; Coffey, Alison J; Middleditch, Claire; Balding, David J; Rogers, Jane; Bentley, David R; Chadwick, David; Johnson, Michael R; et al.
Introduction: Approximately 30% of patients with epilepsy are resistant to treatment with anti-epileptic drugs (AEDs). The ABC drug transporter proteins are hypothesized to mediate drug resistance in epilepsy. More recently, a non-ABC putative transporter, RLIP76, has also been proposed to be involved in the mechanism of pharmacoresistance. One previous association study of six polymorphisms in RLIP76 failed to find any association with drug resistance in a retrospective cohort of epilepsy patients. We aimed to look for an association with outcomes reflecting drug response in a larger prospective cohort, with gene-wide coverage.Patients and methods: We investigated the role of common polymorphisms in RLIP76 in epilepsy pharmacoresistance by genotyping 23 common RLIP76 polymorphisms in a prospective cohort of 503 epilepsy patients, from the standard and new anti-epileptic drugs (SANAD) prospective study of new and old AEDs. A total of 13 of these were tested for association with four outcomes reflecting response to drugs: time to first seizure, time to 12-month remission, time to withdrawal due to inadequate seizure control, and time to withdrawal due to unacceptable adverse drug events.Results: No significant associations, allowing for multiple testing, were found in the whole cohort. There was also no effect in a subgroup of patients on carbamazepine, which is thought to be a RLIP76 substrate, although two polymorphisms were associated with time to first seizure (p = 0.007).Discussion: We failed to demonstrate any association between RLIP76 polymorphisms and four different measures of drug response in the larger cohort, but a subgroup analysis of patients receiving carbamazepine suggested an association that should be investigated further.Conclusions: Our data suggest that common variants in RLIP76 are unlikely to contribute to epilepsy drug response.